Design Of Microcontroller Trainer Based On Internet Of Things (IoT) - Alifia Putri Harkha; Hendra Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The rapid advancement of technology, particularly in the industrial sector, necessitates innovative educational tools to enhance students' practical skills. One crucial aspect of technical education is microcontroller programming, which is fundamental in the development of automation and IoT-based systems. However, conventional learning methods, which rely heavily on theoretical instruction and simulations, present challenges in understanding abstract microcontroller programming concepts. This study aims to design and develop an Internet of Things (IoT)-based microcontroller trainer to support practical learning for students at SMK Negeri 1 Bukittinggi. The research follows the Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The study includes needs analysis, prototype design using simulation tools, hardware development, validation by experts, and a practicality test involving students. Validation results indicate that media experts rated the trainer at 93.08%, while material experts provided an average rating of 83.85%, categorizing the trainer as highly valid. Furthermore, student practicality tests resulted in a 90.36% feasibility score, confirming the trainer's effectiveness in enhancing students' understanding of microcontroller programming. These findings suggest that the developed IoT-based microcontroller trainer is a viable educational tool that aligns with industry demands and modern learning methodologies. Keywords—, Internet of Things, Vocational Education, ADDIE Model, Practical Learning.